Trial Watch: Adoptively transferred cells for anticancer immunotherapy - Carole Fournier (OncoImmunology, 2017)
Immunotherapies aimed at strengthening immune effector responses against malignant cells are growing at exponential rates. Alongside, the impressive benefits obtained by patients with advanced melanoma who received adoptively transferred tumor-infiltrating lymphocytes (TILs) have encouraged the scientific community to pursue adoptive cell transfer (ACT)-based immunotherapy. ACT involves autologous or allogenic effector lymphocytes that are generally obtained from the peripheral blood or resected tumors, expanded and activated ex vivo, and administered to lymphodepleted patients. ACT may be optionally associated with chemo- and/or immunotherapeutics, with the overall aim of enhancing the proliferation, persistence and functionality of infused cells, as well as to ensure their evolution in an immunological permissive local and systemic microenvironment. In addition, isolated lymphocytes can be genetically engineered to endow them with the ability to target a specific tumor-associated antigen (TAA), to increase their lifespan, and/or to reduce their potential toxicity. The infusion of chimeric antigen receptor (CAR)-expressing cytotoxic T lymphocytes redirected against CD19 has shown promising clinical efficacy in patients with B-cell malignancies. Accordingly, the US Food and Drug Administration (FDA) has recently granted ‘breakthrough therapy’ designation to a CAR-based T-cell therapy (CTL019) for patients with B-cell malignancies. Considerable efforts are now being devoted to the development of efficient ACT-based immunotherapies for non-hematological neoplasms. In this Trial Watch, we summarize recent clinical advances on the use of ACT for oncological indications.